Broiler Performance From Cull Eggs - Gary D. Butcher; Amir H. Nilipour (EDIS)
In a commercial broiler integration, the objective is to provide the best quality hatching eggs that produce the greatest number of quality chicks per hen housed. A properly managed hen can produce more than 180 eggs, which potentially can result in approximately 600 pounds of broiler meat. However, there exists great variation in the amount of meat produced per hen among integrations. Much of this difference can be traced back to how the eggs were managed during collection, storage, and incubation. The production goals of an integration can be achieved when basic concepts of optimum fertile egg selection and grading, plus common sense management, are considered. This document is VM125, one of a series of the Animal Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date April 29, 2002.